Internationaler Kunstmarkt Köln 1977. - von Berswordt-Wallrabe, Alexander (Köln : Messe- und Ausstellungs-Ges.m.b.H., 1977)
Abrahams, Ivor ; Abramovic, Marina & Ulay ; Adler, Jankel ; Alfaro ; Anczykowsky, Gisela ; Arman ; Avramidis, Joannis ; Barnim ; Barth, Jim ; Baumeister, Willi ; Bayer, Herbert ; Benow, Sheila ; Berrocal, Miguel ; Bierhoff, Fritz ; Bill, Max ; Boernieck ; Bramer, Josef ; Breker, Arno ; Bruni, Bruno ; Bühl, Hede ; Buthe, Michael ; Buttini, Roberta ; Caddick, Kathleen ; Camille, Graeser ; Chagall, Marc ; Claassen, Udo ; Costa, Amleto dalla ; d'Armagnac, Ben ; Dahmen, Karl Fred ; Dali, Salvador ; demel, Karel ; Denk, Wolfgang ; van Doesburg, Theo ; Dressler, Otto ; Dubuffet, Jean ; Edelmann, Yrjö ; Eichenberger, Charles ; Ernst, Max ; Fräger, Wolfgang ; Francis, Sam ; Fuchs, Ernst ; Gernhardt, Per ; Gerz, Jochen ; Gladwell, Guy ; Goller, Bruno ; Grosz, George ; Guacci, Italo ; Van Hall, Maja ; Harter, Eric ; Havard, James ; Van Heel, Jan ; Heyward, Julia ; Hockney, David ; Hoke, Giselbert ; Hubbuch, Karl ; Hübel ; Hurtig, Britta ; Ikonomou, Stathis ; Janko, Lika ; Janssen, Horst ; Jaranow, Atanas ; Jawlensky, Alexej von ; Kandinsky, Wassily ; Kausch, Werner ; Klauke, Jürgen ; Krug, Bernhard ; Lebasque, Henry ; Lennep, Jacques ; Mack, Heinz ; Magnus, Carl ; Mantovani, Adelchi-Riccardo ; Marcks, Gerhard ; Mariani, Carlo Maria ; Matouschek, Richard ; Meckseper, Friedrich ; Miro, Joan ; Mitzka, Ernst ; Monnier, C. ; Moore, Henry ; Morley, Malcolm ; Müllerstaedt ; Neuhaus, Josef ; Nolde, Emil ; Nückel, Otto ; Oasis, Prupes ; Picasso, Pablo ; Piene, Otto ; Pion, Dr. Emil ; Polke, Sigmar ; Van Rafelghem, Paul ; Raufuss ; Reineking, James ; Renger-Patzsch, Albert ; Riedl, Alois ; Scherzer, Greta-Maria ; Schiele, Egon ; Schmidt-Rottluff, Karl ; Schwitters, Kurt ; Serra, Richard ; Settanni, Pino ; Shapiro, Shmuel ; Simetti, Turi ; Skricka, Ernst ; Smith, Jack ; etc.
Duits & Engels
Internationaler Kunstmarkt Köln 1977, 26. - 31.10.1977
boek